Medical Colostomy: A New Resource - Hernández, José Luis García; Cabello, José de Jesús Urbina; Barrón, Gema Méndez; Suárez, Ivonne Alondra León; Segura, Carlos Andrés Salas; Medina, Myrna Sofía Hernández; Sánchez, Morelos Adolfo García (British Journal of Healthcare and Medical Research, 2025)
Introduction: colostomy comes from the Latin and Greek root: colum which means part of the large intestine as well stomatos "mouth or orifice". Objective: To describe the patients' experience of the use of medical colostomy with the respective indications for emergencies and scheduled surgical interventions. Method: retrospective, longitudinal, observational and descriptive multicenter study regarding the use of medical colostomy in patients with well-established indications for urgent/scheduled surgeries. Results: of 176 patients with 85 (48.29%) men and 91 women (51.70%), with an average age of 34, bimodal value of 20 and 44 years, the medical colostomy methodology was applied in scheduled surgery 87% and the rest in emergency. Discussion: in the first 3 months after ostomy creation, the diameter and height of the ostomy typically decrease, and changes in body weight or other modifications regarding the shape of the ostomy can alter the peristomal area, resulting in deep folds and wrinkles, bulging, and inward/outward body profiles. Conclusions: the medical colostomy, with its well-described indications, becomes a new watershed as an option in terms of being an innovative, effective, economical, safe and even preferential therapeutic resource; minimizing morbidity and mortality, with a better prognosis for the patient.